2017
DOI: 10.1121/1.5001491
|View full text |Cite
|
Sign up to set email alerts
|

A fully automated approach for baby cry signal segmentation and boundary detection of expiratory and inspiratory episodes

Abstract: The detection of cry sounds is generally an important pre-processing step for various applications involving cry analysis such as diagnostic systems, electronic monitoring systems, emotion detection, and robotics for baby caregivers. Given its complexity, an automatic cry segmentation system is a rather challenging topic. In this paper, a framework for automatic cry sound segmentation for application in a cry-based diagnostic system has been proposed. The contribution of various additional time- and frequency-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…The accuracy rates for classification tasks between healthy infants and infants with asphyxia were reported to be 93.16-94%, respectively. Moreover, anger, pain, and fear detection from cry signals were carried out, yielding a recognition rate of 90.4% [2]. The facts support our choice of data mining techniques and verify the distribution of registered cries into the aforementioned two categories.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The accuracy rates for classification tasks between healthy infants and infants with asphyxia were reported to be 93.16-94%, respectively. Moreover, anger, pain, and fear detection from cry signals were carried out, yielding a recognition rate of 90.4% [2]. The facts support our choice of data mining techniques and verify the distribution of registered cries into the aforementioned two categories.…”
Section: Discussionsupporting
confidence: 57%
“…The NBs cry has been the object of research and analysis for many years. Researchers found numerous variables that sustain the fact that cry signals can provide relevant information about the physical and psychological states of the NB [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Although the feasibility of audio-based infant cry detection has been investigated, there are still limitations. For instance, data used in those previous studies were either recorded in a controlled environment with a fixed microphone placement [6], manually selected with a good balance between cry and non-cry sounds [8], [10], or having relatively short recordings [9], [11]. Algorithms developed on such data are likely impractical for long-term home monitoring with the presence of other baby voices (such as moaning or whining, coughing, and laughing) and various sounds (caused by, e.g., human talking, music, and car engine), as well as with different microphone placements depending on the layout of the baby room and the own preference.…”
Section: Introductionmentioning
confidence: 99%
“…The classification of full-term and preterm infant cry is presented in [12]. Recently, an automatic cry segmentation system is proposed as a pre-processing step in the infant cry classification task [13]. Other notable studies for infant cry classification include the works reported in [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%